2018
DOI: 10.1002/jcp.27794
|View full text |Cite
|
Sign up to set email alerts
|

α‐2‐Macroglobulin induces the shedding of microvesicles from cutaneous wound myofibroblasts

Abstract: Microvesicles (MVs) are recognized as an important class of cell‐to‐cell messengers. Although the properties of MVs are increasingly documented, the mechanisms regulating MV biogenesis remain debated. Myofibroblasts are a key cellular component of wound healing and have been shown to produce MVs upon stimulation with serum. However, the mediator(s) responsible for the observed effect of serum on MV release have yet to be identified. To isolate the molecule(s) of interest, serum proteins were sequentially separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…[25,26] Our results suggest, however, shedding from Wmyos in our recent work on intercellular communication in normal skin repair. [7] In the present study, we demonstrated that A2M, at concentrations within the physiological range, enhances MV production by Hmyos in a dose-dependent manner. Although a certain amount of A2M accumulates in dermal tissue following any cutaneous injury, hypertrophic scars and lesions of thermal origin are characterized by excessive inflammation and increased extravasation of serum proteins, including A2M, into the wound bed.…”
Section: Blockade Of the A2m-lrp1 Interaction Inhibits MV Shedding supporting
confidence: 63%
See 3 more Smart Citations
“…[25,26] Our results suggest, however, shedding from Wmyos in our recent work on intercellular communication in normal skin repair. [7] In the present study, we demonstrated that A2M, at concentrations within the physiological range, enhances MV production by Hmyos in a dose-dependent manner. Although a certain amount of A2M accumulates in dermal tissue following any cutaneous injury, hypertrophic scars and lesions of thermal origin are characterized by excessive inflammation and increased extravasation of serum proteins, including A2M, into the wound bed.…”
Section: Blockade Of the A2m-lrp1 Interaction Inhibits MV Shedding supporting
confidence: 63%
“…MV production was quantified by autofluorescence emission spectra analysis as previously described. [ 7 ] Briefly, after 24 hours of treatment, MVs were isolated from cell culture supernatants by centrifugation at 21 000 × g for 20 minutes at 4°C. Concurrently, the cells were trypsinized and pelleted by centrifugation at 300 × g for 5 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional cell surface receptors are involved in microvesicle secretion, including G protein-coupled receptor 30 [81], α-2-Macroglobulin receptor [82], transient receptor potential vanilloid type 1 [88] and tissue factor [83]. In addition, microvesicle secretioin is also induced by intratumoral hypoxia, which transcriptionally regulates the expression of the small GTPase Rab22A that colocalizes with budding MVs [84].…”
Section: Microvesicle Biogenesis and Releasementioning
confidence: 99%